Design, Synthesis and Anticancer Evaluation of Oxa/Thiadiazolylhydrazones of Barbituric and Thiobarbituric Acid: A Collective In Vitro and In Silico Approach. Issue 25 (2nd July 2018) - Bhatt, Priyanka; Kumar, Manoj; Jha, Anjali
Abstract: A series of hybrid analogs of barbituric/thiobarbituric acid and 1, 3, 4‐oxa/thiadiazoles were synthesized by a sequence of diazotization and coupling reaction. Structures of all the synthesized compounds were confirmed by IR, NMR and mass spectroscopy. All the compounds were tested by in vitro 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide (MTT) based assay against two human cancer cell lines: human breast adenocarcinoma cell line MCF‐7 and colorectal adenocarcinoma cell line HT‐29. Compound11 which contained 1, 3, 4‐thiadiazole ring, p ‐NO2 ‐phenyl group and thiobarbituric acid moiety displayed activity better than that of the standard drug Doxorubicin (DOX) used in the study. Target hunting and computational docking studies were used to explain the interactions between compound11 and the potential targets. Abstract : A small library of hybrid analogs of barbituric/thiobarbituric acid and1, 3, 4‐oxa/thiadiazoles was synthesized and tested against human breast (MCF‐7) and colorectal (HT‐29) cancer cell lines. Compound11 displayed better activity than standard drug DOX against both the cell lines. Computational modeling experiments were performed to get insight at molecular level.